(untitled) (Clinics, 2015)
Patients frequently experience postoperative pain after a total knee arthroplasty; such pain is always challenging to treat and may delay the patient’s recovery. It is unclear whether local infiltration or a femoral nerve block offers a better analgesic effect after total knee arthroplasty.We performed a systematic review and meta-analysis of randomized controlled trials to compare local infiltration with a femoral nerve block in patients who underwent a primary unilateral total knee arthroplasty. We searched Pubmed, EMBASE, and the Cochrane Library through December 2014. Two reviewers scanned abstracts and extracted data. The data collected included numeric rating scale values for pain at rest and pain upon movement and opioid consumption in the first 24 hours. Mean differences with 95% confidence intervals were calculated for each end point. A sensitivity analysis was conducted to evaluate potential sources of heterogeneity.While the numeric rating scale values for pain upon movement (MD-0.62; 95%CI: -1.13 to -0.12; p=0.02) in the first 24 hours differed significantly between the patients who received local infiltration and those who received a femoral nerve block, there were no differences in the numeric rating scale results for pain at rest (MD-0.42; 95%CI:-1.32 to 0.47; p=0.35) or opioid consumption (MD 2.92; 95%CI:-1.32 to 7.16; p=0.18) in the first 24 hours.Local infiltration and femoral nerve block showed no significant differences in pain intensity at rest or opioid consumption after total knee arthroplasty, but the femoral nerve block was associated with reduced pain upon movement.